2008
DOI: 10.1021/jo801457r
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Adducts of N-Heterocyclic Carbenes: Thermal Stability and Catalytic Activity toward the Coupling of CO2 with Epoxides

Abstract: Thermal stability of CO2 adducts of N-heterocyclic carbenes (NHCs) was studied by means of in situ FTIR method with monitoring of the nu(CO2) region of the infrared spectra under various conditions. 1,3-Bis(2,6-diisopropylphenyl)imidazolinium-2-carboxylate (SIPr-CO2) shows higher thermal stability compared with 1,3-bis(2,6-diisopropylphenyl)imidazolium-2-carboxylate (IPr-CO2). The presence of free CO2 can significantly inhibit the decomposition of NHC-CO2 adducts, while the addition of an epoxide such as propy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
188
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(199 citation statements)
references
References 57 publications
9
188
0
Order By: Relevance
“…If the complex has a low-valent, nucleophilic metal locus, then CO 2 coordination occurs as an g 2 -CO 2 complex with the metal bound to the central carbon to form a carboxylate (36). This particular type of coordination is also observed in the presence of organic nucleophiles as described in Section 3.3 and is of particular interest in the field of electrocatalysis for CO 2 reduction with molecular species.…”
Section: Lewis-acid/base Activation and Catalysismentioning
confidence: 92%
See 1 more Smart Citation
“…If the complex has a low-valent, nucleophilic metal locus, then CO 2 coordination occurs as an g 2 -CO 2 complex with the metal bound to the central carbon to form a carboxylate (36). This particular type of coordination is also observed in the presence of organic nucleophiles as described in Section 3.3 and is of particular interest in the field of electrocatalysis for CO 2 reduction with molecular species.…”
Section: Lewis-acid/base Activation and Catalysismentioning
confidence: 92%
“…Thermal stability studies have yielded a series of data shown in Fig. 3 [35,36]. From the available data, we have observed a trend in the temperature (T) of CO 2 release of these zwitterionic species.…”
Section: C1-carriers In Nature: Folate Chemistrymentioning
confidence: 99%
“…59 Being highly nucleophilic in nature, NHCs need to bind suitable electrophiles to form air-and moisture-stable adducts: a classic example is the formation of a zwitterionic NHC−CO 2 adducts (Scheme 3). 60 These adducts are labile in solution, making them suitable for catalytic turnover.…”
Section: N-heterocyclic Carbenes (Nhcs)mentioning
confidence: 99%
“…The nucleophilic attack of the CO 2 moiety bound to the NHC on the substrates is thought to be the rate-limiting step: this hypothesis seems to be supported by a significant positive effect of electron-donating alkyl substituents on the NHC heteroatoms. Previously, Lu and coworkers 60 reported on the use of 1,3-diarylimidazolium-2-carboxylates as catalysts in similar transformations. At a later stage, the same group has shown that a NHC-CO 2 adduct could also be immobilized on a MCM-41 support and the catalytic activity of this hybrid material in the coupling between CO 2 and epoxides was investigated.…”
Section: Scheme 11 Azaphosphatranes Acting As Catalysts In the Couplimentioning
confidence: 99%
“…5 Imidazolium carboxylates have been shown to successfully catalyse reactions such as the coupling of epoxides and carbon dioxide to produce cyclic carbamates. 6 The more Lewis basic nature of imidazolium dithiocarboxylates has allowed them to be used successfully as catalysts for the cyanosilylation of aldehydes, 7 and in the Staudinger reaction to prepare β-lactams. 8 Delaude demonstrated that the NHC·CS 2 can also be used as ligand and coordinates as a κ 2 ,S,S′ chelate to the Ru II centre in the first examples of transition-metal complexes with such ligands (B in Chart 1).…”
mentioning
confidence: 99%